The new knowledge workers - Jemielniak, Dariusz (New horizons in management, 2012)
The book is a cross-cultural, comparative study of American and European high-tech workplaces that addresses the issues currently of interest to both Academia and to practice and provides a rare international comparison of organizations from both sides of the Atlantic. Its conclusions shed new light on the problems typical for software projects. The book specifically focuses on, and gives voice to, the perspectives of knowledge workers rather than managers and will thus be useful to not only scholars and human resource managers from software companies, but also to high-tech professionals.